A comparative study on the wear behavior of a polymer infiltrated ceramic network (PICN) material and tooth enamel. Issue 12 (December 2017) - Xu, Zhou; Yu, Ping; Arola, Dwayne D.; Min, Jie; Gao, Shanshan
Highlights: The damaging mode of PICN in the wear process has been studied. The PICN shows a wear damaging mode similar to tooth enamel. The wear resistance of the PICN is worse than tooth enamel. Abstract: Objective: To investigate the wear mechanisms of a polymer infiltrated ceramic network (PICN) material, to compare its wear behavior with that of tooth enamel, and to provide evidence relevant to its clinical use. Methods: The Vickers hardness (HV) and elastic modulus (E) of a commercial PICN material (ENAMIC) and enamel were measured. Reciprocating wear tests were performed under a ball-on-flat configuration. Three wear pairs were explored including ENAMIC and enamel subjected to Si3 N4 ball antagonists and ENAMIC subjected to enamel cusp antagonists. The coefficients of Friction (CoFs) were monitored continuously to 5 × 10 4 cycles. The wear depth of ENAMIC, enamel specimens and enamel cusps were quantified using white light interferometry, and the wear morphologies were examined using scanning electron microscopy (SEM) to distinguish the wear mechanisms. Results: The HV of ENAMIC is similar to tooth enamel but the E is much lower. For both materials, the CoFs increased sharply in the early stage and then reached plateaus in the later phase. Throughout the cyclic loading history, ENAMIC exhibited larger wear depths than enamel. However, the damage evolution in ENAMIC was similar to that of enamel as the polymer phase was worn preferentially similar to inter-rod enamel, and then the ceramic phase exfoliated from the wear surface akin to enamel rods. The SEM images showed evidence of few cracks within wear tracks of ENAMIC, in comparison to numerous cracks in tooth enamel. Significance: ENAMIC has lower wear resistance than tooth enamel, but it exhibits a wear damage mode similar to tooth enamel.